2022
DOI: 10.1097/fjc.0000000000001206
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin D Alleviates DOX-induced Cardiac Injury In Vivo and In Vitro

Abstract: :As a highly efficient anticancer agent, doxorubicin (DOX) is used for treatment of various cancers, but DOX-induced oxidative damages contribute to a degenerative irreversible cardiac toxicity. Saikosaponin D (SSD), which is a triterpenoid saponin with many biological activities including anti-inflammatory effects and antioxidant properties, provides protection against pathologic cardiac remodeling and fibrosis. In the present study, we investigated the work of SSD for DOX-induced cardiotoxicity and the invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A previous study reported that SSA alleviated pressure overload-induced cardiac fibrosis ( 14 ). Zhang et al ( 45 ) reported that Saikosaponin D, another similar triterpenoid saponin isolated from R. bupleuri , efficiently protected cardiomyocytes from Doxorubicin-induced cardiotoxicity by inhibiting excessive oxidative stress. In addition, SSA has a protective effect on the kidney ( 15 ) and complications of chronic kidney disease ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that SSA alleviated pressure overload-induced cardiac fibrosis ( 14 ). Zhang et al ( 45 ) reported that Saikosaponin D, another similar triterpenoid saponin isolated from R. bupleuri , efficiently protected cardiomyocytes from Doxorubicin-induced cardiotoxicity by inhibiting excessive oxidative stress. In addition, SSA has a protective effect on the kidney ( 15 ) and complications of chronic kidney disease ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chai Hu polysaccharide, the main active ingredient in Chai Hu, has significant in vitro antioxidant effects, and it can significantly delay hydrogen peroxide (H2O2)-induced senescence in mouse lung epithelial cells [135]. Chaihu saponin D can regulate PI3K/NRF2, p38-MAPK signaling pathway and thus inhibit senescence in each cell by reducing oxidation levels in studies based on neuronal cell inflammation, cardiomyocyte inflammation, and hose cell inflammation [136][137][138].…”
Section: Bupleurum Scorzonerifolium and Its Compounds Delay Cellular ...mentioning
confidence: 99%
“…Saikosaponin D has been shown to reduce DOX-induced LDH leakage, cardiomyocyte apoptosis, myocardial fibrosis, and reduction in cardiomyocyte size in mice. Saikosaponin D can increase levels of endogenous antioxidant enzymes, reduce levels of MDA and ROS to inhibit excessive oxidative stress, and protect cardiomyocytes from DOX-induced cardiotoxicity by inhibiting the p38-MAPK signaling pathway [282].…”
Section: Saponinsmentioning
confidence: 99%